The last crusade: time and historicity in Brasil Paralelo's documentary series (Tempo e Argumento, 2023)
This article aims to analyze the time experiences and historicity forms implied in the production of the series “Brasil: A Última Cruzada”, released by the company Brasil Paralelo. Created in 2016 with the goal of offering an alleged intellectual discourse to the new Brazilian right-wing movements, the producer has in the negationist narrative on History of Brazil one of its most prominent scopes of work. This article investigates the way this audiovisual discourse manipulates temporal experiences available in contemporaneity, articulating a discourse marked by the historicist chronotope that points to a historical philosophy with Christian and eurocentric roots, and an updatist conduct guided by self-centred temporal experience and entrepreneurial rhetoric, which reduces the multiplicity of times to a search for past entrepreneurs.
Keywords: negationism; historicity; historicism; updatism; history of Brazil